PERENCANAAN PERSEDIAAN UNTUK MATERIAL KOMPRESOR MENGGUNAKAN ECONOMIC ORDER QUANTITY PROBABILISTIK PADA PRODUK AIR CONDITIONER - Nirfison Nirfison (Universitas Mercu Buana, 2017)
Companies always try to reduce inventory to make capital turnover running smoothly and don’t want to keep the inventory long time. However, inventory cannot be directly reduced as low as there are risks for production that can be material shortages and the can lose the sales. It is necessary to control the business to obtain the optimum inventory value. This research discusses the material inventory problem in air conditioner (air conditioner) which aims to find out efficient inventory control method in order to reduce total inventory cost. This research uses probabilistic EOQ (Economic Order Quantity) method. The focus of the problem studied is the inventory of compressor materials that contribute most to the value of purchases and the resulting inventory. This research tries to give optimal EOQ value for every order, ROP (Reorder Point), safety stock and total inventory cost. Based on the calculation the total inventory cost of the compressor material calculated using this probabilistic EOQ method resulted in a total cost reduction of 8.2% compared to the total inventory cost generated by company policy.